2022
DOI: 10.1108/lhs-06-2022-0067
|View full text |Cite
|
Sign up to set email alerts
|

Knowing, relating and the absence of conflict: relational leadership processes between hospital boards and chairs of nurse councils

Abstract: Purpose This study aims to enhance understanding of the collaboration between chairs of nurse councils (CNCs) and members of executive hospital boards (BM) from a relational leadership perspective. Design/methodology/approach The authors used a qualitative and interpretive methodology. The authors study the daily interactions of BM and CNCs of seven Dutch hospitals through a relational leadership lens. The authors used a combination of observations, interviews and document analysis. The author’s qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…Second, nursing professionals can improve their positions by working together with others, both within and outside the nursing profession, toward shared goals. Instead of merely focusing on what nurses themselves should do to achieve change, focusing on finding out which people they need “on their side” might be more beneficial (see also Verhoeven et al, 2022). NCSs did not work alone to achieve change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, nursing professionals can improve their positions by working together with others, both within and outside the nursing profession, toward shared goals. Instead of merely focusing on what nurses themselves should do to achieve change, focusing on finding out which people they need “on their side” might be more beneficial (see also Verhoeven et al, 2022). NCSs did not work alone to achieve change.…”
Section: Discussionmentioning
confidence: 99%
“…Leadership is not an individual but a relational practice. Collaborating with others is key to successfully achieving change (e.g., Verhoeven et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our view, this conflict is connected to rebel nurse leadership practices, because nurses experience internal conflicts that stimulate rebel leadership behavior. In contrast, research has also shown that discussing conflicting perspectives supports collaboration and the building of collective leadership in complex practices (Follet, 2011; Streeton et al, 2021; Uhl‐Bien et al, 2020; Verhoeven et al, 2022). We noticed that speaking up and discussing conflicting perspectives and dilemmas in daily practice helped nurses and nurse managers find a collaborative perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of talk has been acknowledged for frontline nursing work (Barcelona et al, 2023;Dahlke & Hunter, 2020;Lopez-Deflory et al, 2023b;Marey-Sarwan et al, 2022) it seems overlooked in the nursing leadership and governance literature (see Cummings et al, 2021;Kanninen et al, 2021). However, Verhoeven et al (2023) showed that such a discursive leadership perspective can be supportive for comprehending the relational processes and interdependencies between board members and nurses. Therefore, in our study, we focus on such discursive, relational leadership practices (Barge, 2012;Uhl-Bien, 2006) and aim to uncover how these influence the positioning and voicing of nurses, in times of crisis, when interdependency is high (De Graaff et al, 2021).…”
Section: Introductionmentioning
confidence: 99%